POLICY OF THE NATIONAL BANK OF UKRAINE DURING THE WAR - Petryk, Oleksandr (Socio-economic relations in the digital society, 2022)
The russian invasion led to terrible human losses and suffering, and catastrophic consequences for Ukraine's economy. A large part of the country's territory was occupied, many key enterprises and businesses were ruined or completely destroyed. Towards the winter, the country faced a series of continuous missile attacks, that destroyed critical infrastructure and killed civilians. Millions of Ukrainians were forced to move to safer regions of Ukraine or went abroad. In these conditions, it was important to ensure financial stability, smooth functioning of banking and payment systems, and smooth operation of state finances and the financial system in general.The article defines the primary tasks of the National Bank of Ukraine in the conditions of military aggression unleashed by russia against Ukraine. The most important aspects of the functioning of the National Bank to ensure the uninterrupted operation of the financial system and the financial stability of the economy, in general, have been studied. The dynamics of the main macroeconomic indicators of the Ukrainian economy were analyzed. The main problems of monetary and currency policy are characterized, and further steps to implement the tasks of the financial regulator are determined.
Keywords: macroeconomic indicators; monetary policy; exchange rate policy; financial stability; financial system